2012
DOI: 10.1021/jm300542e
|View full text |Cite
|
Sign up to set email alerts
|

Novel Trisubstituted Harmine Derivatives with Original in Vitro Anticancer Activity

Abstract: To overcome the intrinsic resistance of cancer cells to apoptotic stimuli, we designed and synthesized approximately 50 novel β-carbolines structurally related to harmine. Harmine is known for its anticancer properties and is a DYRK1A inhibitor. Of the synthesized compounds, the most active in terms of growth inhibition of five cancer cell lines are cytostatic and approximately 100 times more potent than harmine but demonstrated no DYRK1A inhibitory activity. These novel β-carbolines display similar growth inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 52 publications
1
67
0
Order By: Relevance
“…SAR studies confirmed that substituents in position 2 and 9 displayed an important role in modulation of antitumor activities [134]. Derivatives of 59 that possess in R1, R2, and, R3 (Figure 11) a benzyl and 3'-fluorobenzyl groups are more likely to act as protein synthesis inhibitors [137].…”
Section: Harmine and Derivativesmentioning
confidence: 81%
“…SAR studies confirmed that substituents in position 2 and 9 displayed an important role in modulation of antitumor activities [134]. Derivatives of 59 that possess in R1, R2, and, R3 (Figure 11) a benzyl and 3'-fluorobenzyl groups are more likely to act as protein synthesis inhibitors [137].…”
Section: Harmine and Derivativesmentioning
confidence: 81%
“…H NMR spectrum of compound 5a, as an example, compared with that of the hydrazide 3 used as a starting material, allowed us to note in addition to the signals relative to protons introduced by the hydrazide 3, the presence of two multiplets at d H 1.61 (4H, m, 2CH 2 ) and 1.24 (4H, m, 2CH 2 ) corresponding to the four methylene groups introduced by the anhydride and the disappearance of the signal related to the NH 2 protons at d H 4.38 (of intermediate 3). This structure was also evidenced by the observation in the 13 C NMR spectrum of characteristic signal at d C 167.4 corresponding to the two carbonyls of the amide functions. The same spectrum revealed three signals at d C 37.6 (2CH), 23.1 (2CH 2 ) and 21.0 (2CH 2 ) easly attributable to the methine and the two methylene groups of the anhydride moiety.…”
Section: Ache Inhibitory Activity Assaymentioning
confidence: 62%
“…1 H (300 MHz) and 13 C (75 MHz) NMR spectra were recorded on a Bruker AM-300 spectrometer, using CDCl 3 , CD 3 OD and DMSO-d 6 as solvent and non-deuterated residual solvent as internal standard. Chemicals shifts (d) are given in parts per million (ppm) and coupling constants (J) in Hertz.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Time-lapse acquisition of phase contrast microscopy pictures was automatically recorded every 4 min over a 72 h period in triplicate. 30,46−48 Quantitative data have been obtained by the counting of the number of cells on the pictures over time as previously described 30,46,48 and detailed in the legends of the figures. MTT Colorimetric Assay.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%